PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV-A PADA MATERI SUMBER ENERGI ALTERNATIF DI SD KRISTEN GLORIA 3 SURABAYA - Andreas Armando Prastowo; Yuni Gayatri; Ni Luh Putu Sari Murthi (PROCEEDING UMSURABAYA, 2024)
This study aims to improve the learning outcomes of class IV-A students at Gloria 3 Christian Elementary School through the application of the Project Based Learning model on the material of alternative energy sources. The type of research used is pseudo-experimental research. The research design was one group post test only. The subjects of the research conducted were class IV-A students of Gloria 3 Christian Elementary School, totaling 23 people in the 2023/2024 school year. Data collection techniques by means of observation and tests. The research instrument used a learning implementation observation sheet, cognitive test sheet, and product observation sheet. The results of this study indicate that all stages of project-based learning are well implemented. The results of observations of students' attitudes show 100% meet KKTP, the learning outcomes of students show 96% meet KKTP, the results of students' skills in making products 100% meet KKTP. The results of the reflection showed that all students felt happy and could understand the material taught. The conclusion of this study is that the application of the project-based learning model effectively improves student outcomes.